2023
DOI: 10.3390/insects14100826
|View full text |Cite
|
Sign up to set email alerts
|

Diapause Induction, Color Changes, and Supercooling Point of Diapause Larvae of Tetrastichus septentrionalis Yang (Hymenoptera: Eulophidae)

Zhixin Li,
Junrui Shi,
Liyuan Yang
et al.

Abstract: The chalcid wasp Tetrastichus septentrionalis Yang (Hymenoptera: Eulophidae) is one of the dominant pupal parasitoids of Hyphantria cunea (Drury) (Lepidoptera: Erebidae). In this study, the photoperiod’s effect on diapause induction in T. septentrionalis using the alternative host Tenebrio molitor was measured, revealing that T. septentrionalis is of the long-day type. The critical photoperiods for diapause induction in T. septentrionalis were estimated to be between photoperiods of 13:11 and 14:10 (L:D) h at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…During the induction process of diapause in insects, notable changes in physiological characteristics and gene expression often occur. Diapause is sometimes accompanied by changes in body coloration; for example, the chalcid wasp Tetrastichus septentrionalis has two body colors, light yellow in the non-diapause state and gray-brown in the diapause state [11]. For instance, there is an initiation of yolk deposition, an accumulation of lipids in the fat body, and the activation of genes involved in fatty acid synthesis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the induction process of diapause in insects, notable changes in physiological characteristics and gene expression often occur. Diapause is sometimes accompanied by changes in body coloration; for example, the chalcid wasp Tetrastichus septentrionalis has two body colors, light yellow in the non-diapause state and gray-brown in the diapause state [11]. For instance, there is an initiation of yolk deposition, an accumulation of lipids in the fat body, and the activation of genes involved in fatty acid synthesis [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the photoperiod not only causes physiological changes in adults but also has potential effects on larvae. Environmental factors inducing diapause have been widely studied, but there are few reports on the sensitive period of diapause induction [10,11,38]. It has been observed that third-instar larvae and pre-pupae exhibit greater sensitivity compared with other stages of preimaginal development in C. nipponensis [32].…”
Section: Introductionmentioning
confidence: 99%